Co-construction of meaning, creative processes and digital curation: The transmission of music with live electronics. Issue 4 (11th July 2016) - Boutard, Guillaume
Abstract : Purpose: – The preservation and curation of music with real-time or live electronics is challenging. The goal is not to preserve a recording of the performance but to keep the work alive by providing the means to re-perform them. The purpose of this paper is to present the theoretical and practical outcomes of the documentation, dissemination and preservation of compositions with real-time electronics (DiP-CoRE) project. Design/methodology/approach: – The methodology combines methods stemming from work psychology and ergonomics with conceptual frameworks constructed according to grounded theory. Data were collected during a six months' creative process. Subsequent interviews were conducted during confrontations with documents, including observational recordings, sketches and technical specifications. Findings: – This paper demonstrates the relevance of the proposed documentation methodology for the preservation of contemporary music with live electronics, focussing on the notion of intelligibility. It brings into light the multiple perspective of the documentation of the activity in a multi-agent creative process, which encompasses what was done but also what could have been done. Research limitations/implications: – The DiP-CoRE project bring to light connections between the notion of intelligibility, the thickness of the activity and boundary objects. The paper proposes further directions of research in order to embed the designed framework within digital repositories. Practical implications: – The documentation methodology, designed and tested in this paper, proposes a framework for practitioners, building on video-stimulated recall as well as documents produced during the creative process. This framework requires less expertise (but a more important technical setup) than a traditional interview-based documentation framework. It thus provides opportunities for various size organizations to build methodical documentation processes and to further build on distributed expertise with computer-supported collaborative work. Originality/value: – This paper proposes a new interdisciplinary documentation methodology relevant in the artistic domain, which brings together transmission with objects and by practice. It specifically defines the relation between this proposal and a high-level model for digital curation, namely, the mixed methods digital curation model. It further creates a link between documentation best practice and the ongoing research in the tracking of creative processes.